1996
DOI: 10.1063/1.116334
|View full text |Cite
|
Sign up to set email alerts
|

Near-edge x-ray absorption fine structure study of bonding modifications in BN thin films by ion implantation

Abstract: Near-edge x-ray absorption fine structure (NEXAFS) has been used to study the defect content and the bonding modifications induced in BN thin films by ion implantation. The initial films were hexagonal-like BN grown on Si(100) by pulsed laser deposition. Subsequent ion implantation with N2+ at 180 keV induces the formation of a significant proportion of sp3 bonding (cubic-like), and the formation of nitrogen void defects in the remaining sp2 BN. These modifications in the bonding of a film lacking long range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
69
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 0 publications
3
69
2
Order By: Relevance
“…[39][40][41] The X-Z peaks were assigned to a gradual increment of N-vacancies around the B atoms. 25,26 A similar explanation was given in a XANES study of BN nanotubes, while the intense Z peak was suggested to originate from unreacted boron oxide used in the preparation procedure. 42 In another XANES analysis of BN bamboo-like nanotubes and nanothorns, 43 these X-Z p* transitions were assigned to the same N-void defects, but occupied by B in antisite positions.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…[39][40][41] The X-Z peaks were assigned to a gradual increment of N-vacancies around the B atoms. 25,26 A similar explanation was given in a XANES study of BN nanotubes, while the intense Z peak was suggested to originate from unreacted boron oxide used in the preparation procedure. 42 In another XANES analysis of BN bamboo-like nanotubes and nanothorns, 43 these X-Z p* transitions were assigned to the same N-void defects, but occupied by B in antisite positions.…”
Section: Introductionmentioning
confidence: 95%
“…Point defects are thus readily formed as result of the regular synthesis processes in an uncontrolled way, but they can be intentionally generated to modify the characteristics of BN, for instance by irradiation. 25,26 In this sense, the production of well-controlled defect arrangements is of great importance for the fabrication of BN structures with defined properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the B K-edge shows the presence of three peaks (X-Z) at the right of the characteristic h-BN excitonic transition (W), what proves the existence of 1, 2 and 3 oxygen-saturated nitrogen vacancies around B atoms [40,41], respectively. The creation of these N vacancies has been previously described in literature as a result of ion bombardment [42][43][44]. Second, the N K-edge exhibits a sharp peak at 400.9eV assigned to molecular nitrogen, suggesting that N excess in N-rich h-BN might be assimilated in this form.…”
mentioning
confidence: 94%